Impaired inflammatory resolution with severe SARS-CoV-2 infection in leptin knock out obese hamster - Jiang, Ren-Di; Luo, Yun-Zhe; Lin, Hao-Feng; Zheng, Xiao-Shuang; Zeng, Wen-Tao; Liu, Mei-Qin; Deng, Hao-Hao; Wang, Qi; Lai, Ya-Na; Chen, Ying; Guo, Zi-Shuo; Zeng, Ya; et al. (iScience, 2025)
Comorbidities, such as obesity, increase the risk of severe COVID-19. However, the mechanisms underlying severe illnesses in individuals with obesity are poorly understood. Here, we used gene-edited leptin knock out (Leptin−/−) obese hamsters to establish a severe infection model. This model exhibits robust viral replication, severe lung lesions, pronounced clinical symptoms, and fatal infection, mirroring severe COVID-19 in patients with obesity. Using single-cell transcriptomics on lung tissues pre- and post-infection, we found that monocyte-derived alveolar macrophages (MD-AM) play a key role in lung hyper-inflammation, including two unique MD-AM cell fate branches specific to Leptin−/− hamsters. Notably, reduced Trem2-dependent efferocytosis pathways in Leptin−/− hamsters indicated weakened inflammation resolution, consistent with the scRNA-seq data from patients with obesity. In summary, our study highlights the obesity-associated mechanisms underlying severe SARS-CoV-2 infections and establishes a reliable preclinical animal model for developing obesity-specific therapeutics for critical COVID-19. [Display omitted] •Leptin knock out obese hamsters were generated by using CRISPR/Cas9 technology•SARS-CoV-2 infection results in severe pneumonia and death in Leptin−/− obese hamsters•SARS-CoV-2 infection induces attenuated inflammatory resolution in Leptin−/− obese hamsters•Imbalanced Trem1/Trem2 in MD-AMs contribute to obesity-associated severe infection Immune response; Virology; Omics